Resilient Hippocampal Gamma Rhythmogenesis and Parvalbumin-Expressing Interneuron Function Before and After Plaque Burden in 5xFAD Alzheimer’s Disease Model - Mackenzie-Gray Scott, Connie A.; Pelkey, Kenneth A.; Caccavano, Adam P.; Abebe, Daniel; Lai, Mandy; Black, Khayla N.; Brown, Nicolette D.; Trevelyan, Andrew J.; McBain, Chris J. (Frontiers in Synaptic Neuroscience, 2022)
Recent studies have implicated impaired parvalbumin fast-spiking interneuron (PVIN) function as a precipitating factor underlying abnormalities in network synchrony, oscillatory rhythms, and cognition associated with Alzheimer’s disease (AD). However, a complete developmental investigation of potential gamma deficits induced by commonly used carbachol or kainate in ex vivo slice preparations from AD model mice is lacking. We examined gamma oscillations using field recordings in acute hippocampal slices from 5xFAD and control mice, through the period of developing pathology, starting at 3 months of age, when there is minimal plaque presence in the hippocampus, through to 12+ months of age, when plaque burden is high. In addition, we examined PVIN participation in gamma rhythms using targeted cell-attached recordings of genetically-reported PVINs, in both wild type and mutant mice. In parallel, a developmental immunohistochemical characterisation probing the PVIN-associated expression of PV and perineuronal nets (PNN) were compared between control and 5xFAD mice. Remarkably, this comprehensive longitudinal evaluation failed to reveal any obvious correlations between PVIN deficits (electrical and molecular), circuit rhythmogenesis (gamma frequency and power) and Aβ deposits/plaque formation. By 6-12 months, 5xFAD animals have extensive plaque formation throughout hippocampus. However, a deficit in gamma oscillatory power was only evident in the oldest 5xFAD animals (12+ months), and only when using kainate, and not carbachol, to induce the oscillations. We found no difference in PV firing or phase preference during kainate induced oscillations in younger or older 5xFAD mice compared to control and a reduction of PV and PNNs only in the oldest 5xFAD mice. The lack of a clear relationship between PVIN function, network rhythmicity, and plaque formation in our study highlights an unexpected resilience in PVIN function in the face of extensive plaque pathology associated with this model, calling into question the presumptive link between PVIN pathology and Alzheimer’s progression.